1995
DOI: 10.1136/hrt.74.6.650
|View full text |Cite
|
Sign up to set email alerts
|

Disopyramide stress test: a sensitive and specific tool for predicting impending high degree atrioventricular block in patients with bifascicular block.

Abstract: Objective-To study the value of intravenous disopyramide as part of an invasive electrophysiological study in predicting impending high degree atrioventricular block in patients with bifascicular block. Design-An invasive electrophysiological study was performed in the basal state and after the infusion of disopyramide (2 mg/kg body weight). The progression to high degree atrioventricular block was assessed by bradycardia-detecting pacemakers or repeated 12-lead electrocardiogram recordings, or both. Patients-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Total mortality and cardiac These findings were underlined by studies from the 1980s and '90s. [6][7][8] In their study, Martí-Almor and colleagues demonstrated a similar follow-up period of 4.5 years. 9 Their patient cohort was of comparable age (73 AE 9 years vs 75 AE 9 years, respectively) but included more women (33% vs 17%, respectively).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Total mortality and cardiac These findings were underlined by studies from the 1980s and '90s. [6][7][8] In their study, Martí-Almor and colleagues demonstrated a similar follow-up period of 4.5 years. 9 Their patient cohort was of comparable age (73 AE 9 years vs 75 AE 9 years, respectively) but included more women (33% vs 17%, respectively).…”
Section: Discussionmentioning
confidence: 62%
“…This is supported by the fact that nearly half of the patients with negative EP study (45%) later display arrhythmias in the implantable loop recorder. These findings were underlined by studies from the 1980s and ’90s …”
Section: Discussionmentioning
confidence: 81%
“…They were studied with the purpose of identifying substrates for brady-and tachyarrhythmia. 31,32 Patients without syncope were included to assist the definition of the specificity of the applied protocols. Prior to the invasive electrophysiological study, all patients underwent careful history taking, a physical examination, routine laboratory tests, a chest X ray, a symptom-limited bicycle exercise test, and an echo-Doppler examination including assessment of the left ventricular ejection fraction.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Phase 4 block is always infranodal and can be evaluated with His‐bundle recordings by producing bradycardia and pauses by the electrical induction of atrial or ventricular premature beats. However, a positive response to pharmacological challenge with drugs such as procainamide according to published criteria should probably be a class II indication in symptomatic patients without previously documented AV block 20 , 2 …”
Section: Bifascicular and Trifascicular Blocksmentioning
confidence: 99%
“…However, a positive response to pharmacological challenge with drugs such as procainamide according to published criteria should probably be a class II indication in symptomatic patients without previously documented AV block. 20,21 Acute Myocardial Infarction The ACC/AHA/NASPE 2002 guidelines (and the 1999 ACC/AHA guidelines for the treatment of acute myocardial infarction) advocate "persistent and symptomatic AV block" after acute myocardial infarction (MI) as a class I indication for pacing. 1,22 This vague statement ignores the simple fact that any form of AV block in acute MI can be symptomatic before it resolves completely as in inferior MI.…”
Section: Bifascicular and Trifascicular Blocksmentioning
confidence: 99%